Hubungan Riwayat Hipertensi, Kadar Haemoglobin dan Obesitas Dengan Kejadian Preeklampsia pada Ibu Hamil di RSUD Sungai Lilin Kab. Musi Banyuasin Tahun 2019 - Purwanti Purwanti; Siti Aisyah; Sri Handayani (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Preeclampsia is a disease with hypertensive signs of edema and proteinuria arising from pregnancy. The aim of this study was to determine the correlation between history of hypertension, haemoglobin levels and obesity in RSUD Sungai Lilin, Musi Banyuasin District. This study used systematic random samples by dividing the desired sample size using “Random Sampling” method taken from 60 respondents in which 30% of the respondents experienced preeclampsia and 70% of the respondents did not experience preeclampsia. Respondents suffering from hypertension were 21.7% and respondents not suffering from hypertension were 78.3%. Respondents suffering from anaemia were 25%, and respondents who did not suffer from anaemia were 75%. Meanwhile, respondents who were obese were as much as 8.3% and respondents who were not obese were 91.7%. From the results of the Chi-Square statistical test with α significance level of 0.05,  there was a significant correlation between history of hypertension and the incidence of preeclampsia in pregnant women (p value = 0.000); there was a significant relationship correlation between haemoglobin levels and the incidence of preeclampsia in pregnant women (p value = 0.025); and there was a significant correlation between obesity and the incidence of preeclampsia in pregnant women (p value = 0.025)  at RSUD Sungai Lilin, Musi Banyuasin District in 2019. It is recommended that RSUD Sungai Lilin should be more active in providing training for midwives related to the incidence of preeclampsia in pregnant women.